2023
DOI: 10.1038/s41467-023-39429-x
|View full text |Cite
|
Sign up to set email alerts
|

Decoding a cryptic mechanism of metronidazole resistance among globally disseminated fluoroquinolone-resistant Clostridioides difficile

Abstract: Severe outbreaks and deaths have been linked to the emergence and global spread of fluoroquinolone-resistant Clostridioides difficile over the past two decades. At the same time, metronidazole, a nitro-containing antibiotic, has shown decreasing clinical efficacy in treating C. difficile infection (CDI). Most metronidazole-resistant C. difficile exhibit an unusual resistance phenotype that can only be detected in susceptibility tests using molecularly intact heme. Here, we describe the mechanism underlying thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…difficile ; concerningly, plasmid-mediated metronidazole resistance (pMETRO plasmid) has been found and fluoroquinolone-resistant C. difficile has been found to be directly associated with metronidazole resistance [8, 9]. Currently research into vancomycin resistance is being explored, and recently in vivo resistance to fidaxomicin has been described [10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…difficile ; concerningly, plasmid-mediated metronidazole resistance (pMETRO plasmid) has been found and fluoroquinolone-resistant C. difficile has been found to be directly associated with metronidazole resistance [8, 9]. Currently research into vancomycin resistance is being explored, and recently in vivo resistance to fidaxomicin has been described [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CDI are usually treated with antibiotics such as metronidazole, vancomycin and fidaxomicin [7]. Recent studies, however, have established antibiotic resistance within C. difficile; concerningly, plasmid-mediated metronidazole resistance (pMETRO plasmid) has been found and fluoroquinolone-resistant C. difficile has been found to be directly associated with metronidazole resistance [8,9]. Currently research into vancomycin resistance is being explored, and recently in vivo resistance to fidaxomicin has been described [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The Nim enzymes are nitro-reductases that can transfer either six [ 6 ] or two electrons to the nitro group of metronidazole, yielding either an amino or a nitroso imidazole, respectively [ 20 ]. Recently, in vivo and in vitro experiments demonstrated that a nim group enzyme encoded by Clostridioides difficile strains is a nitro-reductase [ 7 ]. In this latter study, it was also confirmed that metronidazole resistance in C. difficile is dependent on hemin [ 32 ] through experiments involving the direct addition of metronidazole to assay its modification by recombinant NimB and by transcriptomic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The best known and most investigated metronidazole resistance mechanism of BFG strains is mediated by the nim genes, a few of which were originally discovered in the 1980s and 1990s [ 5 ]. There are now 12 known homologs of nim (i.e., nimA-L ) that share 50–80% amino acid homologies, and they are all proposed to act as nitro-reductases [ 6 , 7 ]. They have been localized to both the plasmid and chromosome, and they all require an upstream copy of a Bacteroides -specific insertion sequence (IS) element with promoter sequences to function in metronidazole resistance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only two antibiotics, vancomycin (VAN) and fidaxomicin (FDX), are guidelines recommended for C. difficile infection (CDI) ( 2 ), and antimicrobial resistance has been reported to both ( 3 , 4 ). A third antibiotic, metronidazole (MTZ), is no longer a guideline recommended due to decreasing clinical response rates most likely due to antimicrobial resistance ( 5 , 6 ). Although novel therapeutics are in development for CDI, including the recent approval of live biotherapeutic products, only three antibiotics have made it to phase III trials since the approval of FDX in 2011, and none have filed for Food and Drug Administration approval ( 7 12 ).…”
Section: Introductionmentioning
confidence: 99%